2008
DOI: 10.1080/09553000802345928
|View full text |Cite
|
Sign up to set email alerts
|

Radiofrequency radiation does not significantly affect ornithine decarboxylase activity, proliferation, or caspase-3 activity of fibroblasts in different physiological conditions

Abstract: The results did not support effects on the endpoints studied. Furthermore, stressed and stimulated cells were not more sensitive than normal cells to possible RF radiation-induced effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Hirose et al [2006] reported no effects from RF field exposure on annexin V-FITC affinity or expression of apoptosis-related genes in human glioblastoma A172 and human IMR-90 fibroblasts. Höytö et al [2008b] did not observe any effects on caspase 3 activity in L929 fibroblasts after exposure to RF fields. Joubert et al [2006] studied the effects of RF fields on apoptosis in human neuroblastoma SH-SY5Y cells and rat primary cortical neurons.…”
Section: In Vitro Studies On Cancer-relevant Non-genotoxic Effectsmentioning
confidence: 45%
“…Hirose et al [2006] reported no effects from RF field exposure on annexin V-FITC affinity or expression of apoptosis-related genes in human glioblastoma A172 and human IMR-90 fibroblasts. Höytö et al [2008b] did not observe any effects on caspase 3 activity in L929 fibroblasts after exposure to RF fields. Joubert et al [2006] studied the effects of RF fields on apoptosis in human neuroblastoma SH-SY5Y cells and rat primary cortical neurons.…”
Section: In Vitro Studies On Cancer-relevant Non-genotoxic Effectsmentioning
confidence: 45%
“…Höytö et al (2007b) investigated the ornithine decarboxylase (ODC) activity in murine L929 fibroblasts using 872 or 835 MHz RF fields (CW or 50 Hz modulated) at 2.5 or 6.0 W/kg for 2, 8, or 24 h. The study was planned to replicate earlier studies reporting increased ODC activity in L929 cells but no effects were observed. In further studies by the same group, a lack of effects was confirmed in various cell culture conditions (Höytö et al 2008b), and in several secondary cell lines (Höytö et al 2007a) using 872 MHz CW or 217 Hz modulated fields at 1.5, 2.5, 5.0 or 6.0 W/kg. However, ODC activity in rat primary astrocytes was decreased consistently in all experiments performed at two exposure levels (1.5 and 6.0 W/kg), using GSM modulated or CW RF fields (Höytö et al 2007a).…”
Section: Non-genotoxic Effectsmentioning
confidence: 85%
“…Caspase activity following RF exposure has been investigated as a marker of apoptosis in numerous studies using animal and human cells, but few have demonstrated any effect [19,21,[25][26][27][28]30]. In a series of studies, primary cortical neuron cultures from embryonic rats exposed to CW and GSM 900 MHz signals showed no statistically significant difference in caspase activity.…”
Section: Discussionmentioning
confidence: 99%
“…Apoptosis has also been considered as an endpoint in investigations into potential induction of brain damage by RF. Numerous in vitro studies using human cell lines have produced contrasting results [18][19][20][21][22]. Three in vivo studies of animal brain tissue reported no effect of RF on apoptosis [23][24][25].…”
Section: Introductionmentioning
confidence: 99%